The burden of tuberculosis and attributable risk factors in Brazil, 1990-2017: results from the Global Burden of Disease Study 2017 - Francisco Rogerlândio Martins-Melo; Juliana Maria Trindade Bezerra; David Soeiro Barbosa; Mariângela Carneiro; Kleydson Bonfim Andrade; Antonio Luiz Pinho Ribeiro; Mohsen Naghavi; Guilherme Loureiro Werneck (BMC, 2020)
Abstract Background Tuberculosis (TB) continues to be an important cause of fatal and non-fatal burden in Brazil. In this study, we present estimates for TB burden in Brazil from 1990 to 2017 using data from the Global Burden of Diseases, Injuries, and Risk Factors Study 2017 (GBD 2017). Methods This descriptive study used GBD 2017 findings to report years of life lost (YLLs), years lived with disability (YLDs), and disability-adjusted life years (DALYs) of TB in Brazil by sex, age group, HIV status, and Brazilian states, from 1990 to 2017. We also present the TB burden attributable to independent risk factors such as smoking, alcohol use, and diabetes. Results are reported in absolute number and age-standardized rates (per 100,000 inhabitants) with 95% uncertainty intervals (UIs). Results In 2017, the number of DALYs due to TB (HIV-negative and HIV-positive combined) in Brazil was 284,323 (95% UI: 240,269-349,265). Among HIV-negative individuals, the number of DALYs was 196,366 (95% UI: 189,645-202,394), while 87,957 DALYs (95% UI: 50,624-146,870) were estimated among HIV-positive individuals. Between 1990 and 2017, the absolute number and age-standardized rates of DALYs due to TB at the national level decreased by 47.0% and 68.5%, respectively. In 2017, the sex-age-specific TB burden was highest among males and in children under-1 year and the age groups 45-59 years. The Brazilian states with the highest age-standardized DALY rates in 2017 were Rio de Janeiro, Pernambuco, and Amazonas. Age-standardized DALY rates decreased for all 27 Brazilian states between 1990 and 2017. Alcohol use accounted for 47.5% of national DALYs due to TB among HIV-negative individuals in 2017, smoking for 17.9%, and diabetes for 7.7%. Conclusions GBD 2017 results show that, despite the remarkable progress in reducing the DALY rates during the period, TB remains as an important and preventable cause of health lost to due premature death and disability in Brazil. The findings reinforce the importance of strengthening TB control strategies in Brazil through integrated and multisectoral actions that enable the access to prevention, early diagnosis, and timely treatment, with emphasis on high-risk groups and populations most vulnerable to the disease in the country.